(untitled) (Research, Society and Development, 2021)
The study sought to describe and analyze the knowledge of professionals about risk stratification and recommendations for cardiovascular diseases and metabolic disorders. The research has a descriptive character with a quantitative approach, carried out with professionals from 11 Primary Health Care Units of regional III, in Fortaleza-CE, November 2020 to January 2021. The sample was listed by 23 nurses and 15 physicians. Data collection took place through a form, through the interaction of professionals via Google Docs. The analysis took place after evaluating the responses to the questionnaire. Data were organized in the database in Excel. There was a high and very high risk for hypertension/diabetes, about 97.4%, totaling 37 professionals reported having knowledge of the stratification of users in the territory they monitor. Approximately (42.1%) of users are stratified as high risk as the majority of the population in their territory, very high risk with 2.6%, which means a stratified user with very high risk. A total of 39.5%, 15 patients at medium risk. As for the source of information on risk stratification for hypertensive/diabetic patients (71.8%) it has it through the family health strategy team, with around 27 participants, 28.9%, 11 professionals have the information through the Management of the unit or by electronic medical record (fastmedic). The implementation of a health care model ensures effective care, providing self-care, adequate professional assistance at the various levels of care in the network, with Primary Care being responsible for coordinating care and organizing the RAS.